Sistem Keamanan Data Text Dengan Data Encryption Standard (DES) dan Metode Least Significant Bit (LSB) - Pratistha, Indra; Prakoso, Paholo Iman (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
Abstract Current information can be delivered quickly without knowing the geographical boundaries using the internet. However, the information transmitted can be intercepted by the middle of the road which is not desired, then the security of the data actually becomes a very important issue. The development of computer systems and networks and the interconnection through the Internet has increased, of course, require data security and reliable message in order to avoid the attack. To secure internet data or message network necessary cryptographic encryption methods, one method of data encryption that there is a method of data encryption standard (DES) and subsequently inserted into the Lakeside digital images (steganography) using the method of least significant bit (LSB).